Innovation search fields with Lead Users - Cornelius Herstatt; Christian Lüthje; Christopher Lettl (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2001)
Close orientation with the market is essential for innovation success! Although both academics and market research practitioners would generally agree with this statement, alignment with the needs of the customer often results in conservative innovation strategies. Due to their focus on what is currently on offer in the marketplace, customers primarily demand small, step-wise developments - so-called incremental innovations. This dilemma can be overcome through with the help of particularly advanced customers (Lead Users). The Lead User method aids companies in capitalizing on the innovative potential of these highly qualified customers. A case study with the German firm, Johnson & Johnson Medical GmbH, demonstrated that Breakthrough Innovations are achievable this way. – – Kundenorientierung ist entscheidend für den Innovationserfolg! Obwohl dem Wissenschaftler und Praktiker in der Marktforschung grundsätzlich zustimmen dürften, ist mit der konsequenten Ausrichtung auf die Kundenbedürfnisse gleichzeitig der Nachteil einer konservativen Innovationspolitik verbunden. Kunden fördern durch ihre Fixierung auf aktuelle Marktangebot primär kleine Weiterentwicklungen, d.h. inkrementale Innovationen. Dieses Dilemma kann mit Hilfe besonders fortschrittlicher Kunden (Lead User) überwunden werden. Die Lead User Methode hilft Unternehmen dabei, das innovative Potential dieser hochqualifizierten Kunden zu nutzen. Eine Fallanwendung mit der Johnson&Johnson Medical GmbH demonstriert, wie auf diese Weise Ansätze für radikale Innovationen erarbeitet werden können.
urn:nbn:de:gbv:830-opus-1593
Keywords: 650; Produktentwicklung; Produktinnovation; Marktforschung; Lead User